Hvilken rolle skal forskning og udvikling spille for professionsuddannelserne? - Aagaard, Kaare (Tidsskrift for Professionsstudier, 2024)
When the Danish University Colleges in 2013 were awarded the so-called research obligation, they were given an apparently simple, but in practice very difficult task. The difficulty is particularly linked to the fact that the assignment contains both an educational and a practice-oriented purpose and that these purposes in certain respects stand in an opposite relationship to each other. In the article, this contradictory relationship is highlighted through the formulation of two stylized models, each representing their own understanding of the R&D task. In the article’s discussion, arguments for and against the two fundamentally different understandings of the task are pointed out. The final part of the article argues for the need for clear priorities and clarity around the implications of these. Obviously, it is not a question of choosing one or the other of these stylized models, but a matter of finding good ways of balancing the different considerations while also recognizing the trade-offs that any balance point will entail.